A physicochemical perspective of aging from single-cell analysis of pH, macromolecular and organellar crowding in yeast - Sara N Mouton; David J Thaller; Matthew M Crane; Irina L Rempel; Owen T Terpstra; Anton Steen; Matt Kaeberlein; C Patrick Lusk; Arnold J Boersma; Liesbeth M Veenhoff (eLife, 2020)
Cellular aging is a multifactorial process that is characterized by a decline in homeostatic capacity, best described at the molecular level. Physicochemical properties such as pH and macromolecular crowding are essential to all molecular processes in cells and require maintenance. Whether a drift in physicochemical properties contributes to the overall decline of homeostasis in aging is not known. Here, we show that the cytosol of yeast cells acidifies modestly in early aging and sharply after senescence. Using a macromolecular crowding sensor optimized for long-term FRET measurements, we show that crowding is rather stable and that the stability of crowding is a stronger predictor for lifespan than the absolute crowding levels. Additionally, in aged cells, we observe drastic changes in organellar volume, leading to crowding on the micrometer scale, which we term organellar crowding. Our measurements provide an initial framework of physicochemical parameters of replicatively aged yeast cells.